Cyber Security Challenges, its Emerging Trends on Latest Information and Communication Technology and Cyber Crime in Mobile Money Transaction Services - Pallangyo, Hakeem J. (Tanzania Journal of Engineering and Technology, 2022)
This paper investigates the challenges emerging trends on latest Information and Communication Technology and cybercrime in mobile money transaction services in Tanzania. The objective of this is to evaluate the challenges associated with this rapid growth in ICT and to determine factors influencing Cybersecurity readiness and Cybercrimes in mobile money transaction services. Cyber Security plays a significant role in the field of Information and Communication Technology especially on mobile money transaction services. The study recognizes the provision of mobile money services by both telecommunication companies and local banks, the fact is that whenever we think about the cyber security, the first thing that comes to our mind is "cybercrimes" which are increasing extremely day to day and become a threat. Cybercrimes are mostly practiced through both internet and mobile money services. Securing the information has become one of the major challenges in the present day. Various Governments and companies are taking measures in order to prevent these cybercrimes. Besides cyber security remains concern to many. This paper mainly focuses on challenges faced by cyber security on the latest information and communication technology and cybercrime especially in mobile money transaction services in Tanzania. Its latest techniques, ethics and trends that change the face of cyber security. Relevant data was collected from the Forensic Section of the Tanzania Police Force, Mobile banking mobile money agents and users of the mobile-money services. This study also used the Pearson correlation and analysis of variance (ANOVA) to establish different facts and determine whether the independent variables had a combined effect on the dependent variable. The findings of the study revealed that there is a positive and significant correlation between users ' awareness, mobile money agents training, top management support, technical and logical controls and cybersecurity readiness. The study also concluded that effective training programs aimed to enlighten the users and mobile money agents on cybersecurity issues are an important ingredient for cybersecurity readiness in cybercrime in mobile money transaction services. Keywords: Cyber security readiness, cyber-crime, cyber ethics, mobile money agents, social media, cloud computing, android apps